Characteristics and components of children’s and adolescents’ resilience in disasters in Iran: a qualitative study - Mohammadinia, Leila (Int J Qual Stud Health Well-being, 2018)
Children and adolescents are vulnerable in times of disaster and they will suffer more severely if neglected. The concept of resilience differs between cultures, and identifying the components of resilience is essential for decision making and interventions in disasters such as risk management. This study aimed to identify the components of children’s resilience in disasters in Iran. This qualitative study took a content-analysis approach. Data were collected through semi-structured interviews with 23 people and three group meetings. Conventional content analysis was used for data analysis. MAXQDA 10 software was used for classification. The resilience components derived from the data were categorized into two main categories, internal and external, and eight subcategories covering psychological, emotional, cognitive, mental, spiritual, physical, social, and behavioral factors. The results also showed that the nature of resilience is both intrinsic and extrinsic. Recognizing the dimensions of children’s resilience in disasters can lead to a new perspective for authorities and planners in disaster and emergency situations. The results of this study could be used by planners and policymakers to develop interventions to enhance children’s and adolescents’ resilience at the time of disasters, which is also underlined and highlighted by international documents.